Diseño de un hormigón con fibra metálica para pavimento rígido - Bone Muñoz, Erick Lenin (2024)
With this research, what we seek is to improve conventional concrete with concrete with metallic fiber in construction. Concrete, being the most used in construction, has a low tensile strength, which has led us to search for reinforcement methods. These fibers improve the mechanical properties of concrete, increasing its tensile strength, reducing cracking and improving impact resistance. This study proposes a concrete design with metallic fiber for rigid pavement, evaluating its technical and economic feasibility according to the tests carried out in the laboratory, seeking to increase its durability and mechanical resistance especially in pavements that support heavy loads.......